Analysis Of Three Layer Concentric Tube Heat Exchange Using Mathematic Modeling - Rinaldy Valendry (Journal Basic Science and Technology, 2021)
A three-channel concentric pipes heat exchanger is a development or improvement of a two-channel concentric heat exchange apparatus. This study was conducted to determine the output temperature of each channel, and compare the results of theoretical calculations using mathematical modeling of experimental results conducted in the field. So that obtained difference of value between result of experiment to result of theory calculation. In this study have 3 variations of temperature data that is 50 °C, 55°C, and 60 °C with two streams namely CounterFlow and PararellFLow and discharge 2.5 l/minute, while cold fluid with 25 °C discharge 1.5 l/minute. From the above analysis it can be concluded that the temperature of the hot fluid coming out of the APK in the experiment tends to be higher than the temperature of the hot fluid coming out of the APK on theoretical calculations of mathematical modeling methods. Meanwhile, the cold cold fluid temperature coming out of the APK in experimental tends to be lower than the temperature of the cold fluid coming out of the APK on theoretical calculations of mathematical modeling methods.